Study of the Electrical Characteristics, Shock-Wave Pressure Characteristics, and Attenuation Law Based on Pulse Discharge in Water - Dong Yan; Decun Bian; Jinchang Zhao; Shaoqing Niu (Shock and Vibration)
Strong shock waves can be generated by pulse discharge in water. Study of the pressure characteristics and attenuation law of these waves is highly significant to industrial production and national defense construction. In this research, the shock-wave pressures at several sites were measured by experiment under different conditions of hydrostatic pressure, discharge energy, and propagation distance. Moreover, the shock-wave pressure characteristics were analyzed by combining them with the discharge characteristics in water. An attenuation equation for a shock wave as a function of discharge energy, hydrostatic pressure, and propagation distance was fitted. The experimental results indicated that (1) an increase in hydrostatic pressure had an inhibiting effect on discharge breakdown; (2) the shock-wave peak pressure increased with increasing discharge voltage at 0.5 m from the electrode; it increased rapidly at first and then decreased slowly with increasing hydrostatic pressure; and (3) shock-wave attenuation slowed down with increasing breakdown energy and hydrostatic pressure during shock-wave transfer. These experimental results were discussed based on the mechanism described.